Perbedaan Pengaruh Penggunaan Model Pembelajaran Kooperatif Tipe Number Head Together (NHT) dan Team Games Tournament (TGT) Terhadap Prestasi Belajar Matematika Ditinjau dari Jenis Kelamin - Christiana Sri Wahyuni Kustiasih; Sunardi Sunardi; Sri Haryati (Teknodika, 2016)
The purpose of this research is to find out (1) the difference of effect between the NHT, TGT, and Directive learning (DL) models on the mathematics learning achievement. (2) the difference of learning achievement on mathematics between boys and. (3) the interaction of effect between learning model and gender on  mathematics learning achievement. This kind of research is a quantitative one which uses an experimental factorial design. The population of this research are all the 7th grade - 1st semester students of SMP 1 Sidoharjo, Sragen on the Academic Year Of 2015/2016. The sample is determined by taking 3 clsasses at random. The sampling technique uses the Cluster Random Sampling. The experimental group was treated by the NHT and TGT learning models. While the control group was subjected to the directive learning. For the teaching material is used the Algebraic design. The hypothesis testing uses the factorial design 3x2 with Two-Ways Analysis of Variance (Two Ways Anava) technique with different cells. Before, the trial test was conducted. Forth, for the balance testing was used the t-testing. For the reliability testing of the research instrument with internal consistency was used the Kuder Richardson (KR-20) formula, normality test used the lilliefors method, and the homogenity test used the Bartlet method. The result of the data analysis with significance level of 0.05 obtained: (1) FA = 3.641 and Ftable = 3.07, it mean FA > Ftable. The conclusion of HOA test was rejected and H1A was accepted, which means that there is a significant difference between the learning models to the mathematics achievement. (2) FB = 15.197 and Ftable = 3.92, it obtained FB > Ftable. HOB test was rejected and H1B was accepted. It means that there is a significant difference between boys and girls to the mathematics achievement. (3) FAB = 4.353, Ftable = 3.07, obtained FAB > Ftable. HOAB was rejected and H1AB was accepted, it means that there is a significant interaction of effect between gender and learning models to the mathematics achievement at the subject of Algebraic design.